Copyright exceptions : an archivists perspective - Dryden, Jean (WIPO Magazine, ISSN 1564-7854, 2017)
In a world where we are constantly in search of the new, archives information recorded about the everyday activities of governments, businesses, organizations and individuals may, at first sight, seem rather outdated and unappealing. But many of these records have enduring value both to those who create them and to human society. They offer a window on the past, and insights that help shape the future.
Keywords: TEKIJÄNOIKEUS; POIKKEUKSET; ARKISTOINTI; ARKISTOT; SUOJAUS; UUDELLEENKÄYTTÖ; ORPOTEOKSET; LUOTETTAVUUS; CROSS-BORDER